Simulation and evaluation of a phase synchronous inverter for micro-grid system - Rahman, Towfikur; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Mostafa, Mohammad Golam (2015)
The phase synchronous inverter is an electrical inverter device which is synchronizing inverter phase with the micro-grid phase. Generally, DC voltage supply is considered as the input of the DC to AC inverter which is a renewable energy source such as solar panel, wind turbine and battery storage, etc. The three phase three layer phase synchronous inverters are normally utilized in the high power transmission and distribution systems to supply AC voltage to the three phase micro-grid loads. It has a phase synchronous controller, which includes voltage controllers that contain current regulator and DC voltage regulator to get the reference output power for creating the inverter gate pulses. An inverter utilizing a three leg IGBT has been designed and simulated by using MATLAB2014a/Simulink with the Simscape/SimPower-Systems Block Set. The inverter is connected to an input DC source, an output filter and a controller circuit. It has been observed that the output phase of the inverter is synchronized with the micro-grid phase